IMPLIKASI METODE SYEKH WALIYULLAH AL-DAHLAWI DALAM KAJIAN HADIS - Hudori, Ahmad (Ushuluna: Jurnal Ilmu Ushuluddin, 2020)
AbstractSyekh Waliyullah al-Dahlawi is a thinker who is an expert in various fields, such as aqidah, hadith, history, as well as the field of economics itself. He was an independent thinker. His nature of not thinking about himself is really very remarkable. He spent his whole life in Delhi close to the Mughal palace, but he never sought worldly fame and profit. Syekh Waliyullah al-Dahlawi has a very important implication in the study of hadith. It is interesting to study more deeply how the method of hadith study in the view of Syekh Waliyullah al-Dahlawi, As is known, Sheikh Waliyullah al-Dahlawi is a reformer of Islamic thought who originated from India argued that in understanding the hadith should pay attention to the position and function of the Prophet when delivering the hadith. And most importantly how the method conveyed by Syekh Waliyullah al-Dahlawi will provide a significant development to the understanding of hadith